Vous êtes sur la page 1sur 1

4.

(m, m+1) = 1

dk= m and dj= m+1 is we substitute the first expression for m into the second we have dj = (dk) +1 or

d(j-k)=1 now the only way that the product of two integers is 1 is that both factors are ±1.

So d is 1.

5. 5 (m, m+2) by similar reasoning dk = m and dj = m+2 hence d(j-k) = 2. Now the only possibilities
for d are 1 and 2 and both occur. Notice is m is even then m+2 is even and hence d=2, while if m
is odd both m and m+2 and add and thus d must be 1. (e.g. (5,7))

6. (m, n) =1

7 let d= (3m +2, 5m+3) dk= 3m +2 and dj=5m+3

d(j-k)=5m +3 –(3m+2) = 2m +1